Detection and Localization of Defects in Monocrystalline Silicon Solar Cell. (30th May 2010) - Tománek, P.; Škarvada, P.; Macků, R.; Grmela, L.
Abstract : Near-surface defects in solar cell wafer have undesirable influence upon device properties, as its efficiency and lifetime. When reverse-bias voltage is applied to the wafer, a magnitude of electric signals from defects can be measured electronically, but the localization of defects is difficult using classical optical far-field methods. Therefore, the paper introduces a novel combination of electric and optical methods showing promise of being useful in detection and localization of defects with resolution of 250 nm using near-field nondestructive characterization techniques. The results of mapped topography, local surface reflection, and local light to electric energy conversion measurement in areas with small defects strongly support the development and further evaluation of the technique.